A educação ambiental e a igreja evangélica - Costa, Iracy Lima Cazaes (2012)
Since the issues related to environment and ecology have began to enter in the geopolitical sphere of discussions, that involved the rich countries in discussions and agreements to reduce emissions of pollutants, very slowly Christian churches were entering the debate. Currently the debate gained momentum and final state policies have sought education and environmental awareness. Lined in this discussion, this master work of finding professionals seek to thematize the relevance of ecological and environmental issue for the life of the Christian church.